CONTRÃ”LE DAS PRAGAS DO FEIJOEIRO COM DIVERSOS INSETICIDAS E ACARICIDAS - Nakano, O.; Silveira Neto, S.; Carvalho, R. P. L. (REVISTA DE AGRICULTURA, 2016)
CONTRÃ”LE DAS PRAGAS DO FEIJOEIRO COM DIVERSOS INSETICIDAS E ACARICIDAS